Insomnia Symptoms in Patients With Substance Use Disorders During Detoxification and Associated Clinical Features - Grau-López, Lara; Grau-López, Laia; Daigre, Constanza; Palma-Álvarez, Raúl Felipe; Martínez-Luna, Nieves; Ros-Cucurull, Elena; Ramos-Quiroga, Jose Antonio; Roncero, Carlos (Frontiers in Psychiatry, 2020)
Background: Insomnia is highly prevalent in patients with substance use disorders (SUD), and it has been related to a worse course of addiction. Insomnia during detoxification in a hospital has not been adequately studied. This study aims to compare sociodemographic, clinical, and psychopathological characteristics of SUD patients undergoing a detoxification program, by comorbidity and insomnia symptoms. Methodology: We recruited 481 patients who received pharmacological and psychotherapeutic treatment for detoxification. They were evaluated through semi-structured interviews, standardized questionnaires, and a specific sleep log. A bivariate and multivariate analysis of the data was performed. Results: Insomnia was reported by 66.5% patients, with sleep-maintenance insomnia the most frequent issue, followed by early morning awakening and sleep-onset insomnia. Patients with alcohol use disorder and cannabis use disorder had higher prevalence of sleep-onset insomnia. Patients with cocaine and heroin use disorder had higher prevalence of sleep-maintenance insomnia. Independent factors that allowed the identification of insomnia symptoms included being female (OR: 3.43), polysubstance use (OR: 2.85), comorbid anxiety disorder (OR: 2.02), and prior admission for detoxification (OR: 1.22). Conclusions: Insomnia symptoms are very prevalent in patients admitted for detoxification. The diagnosis and therapeutic strategies for the insomnia symptoms should be improved, especially in women and in patients with greater addiction severity and with anxiety disorders.